2019
DOI: 10.1017/s1041610218002041
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases and related risk factors accelerated cognitive deterioration in patients with late-life depression: a one-year prospective study

Abstract: Objectives:Cognitive impairment in late-life depression is common and associated with a higher risk of all-cause dementia. Late-life depression patients with comorbid cardiovascular diseases (CVDs) or related risk factors may experience higher risks of cognitive deterioration in the short term. We aim to investigate the effect of CVDs and their related risk factors on the cognitive function of patients with late-life depression.Methods:A total of 148 participants were recruited (67 individuals with late-life d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…There are some studies that have showed that the presence of particular aspects, or some diseases, in hypertensive population confers a greater risk of cognitive impairment. This is the case of hypertensive patients with depression (49,50), or hypertensive population with a worse economic situation (51). In general population, many others factors such as depression, educational level, socioeconomic status (rural areas, low income, less social participation), physical inactivity or unhealthy diet have also been related to the development of cognitive impairment (3,(52)(53)(54)(55).…”
Section: Other Factors Related To High Bp and Risk Of Developing Cognmentioning
confidence: 99%
“…There are some studies that have showed that the presence of particular aspects, or some diseases, in hypertensive population confers a greater risk of cognitive impairment. This is the case of hypertensive patients with depression (49,50), or hypertensive population with a worse economic situation (51). In general population, many others factors such as depression, educational level, socioeconomic status (rural areas, low income, less social participation), physical inactivity or unhealthy diet have also been related to the development of cognitive impairment (3,(52)(53)(54)(55).…”
Section: Other Factors Related To High Bp and Risk Of Developing Cognmentioning
confidence: 99%